Level of Respiratory Transmitting Infection Based on Physical Sanitation of the House of Toddler in the Village Punjul Plosoklaten Kediri Regency - Hariyono; Nuranti , Isti Ema; Wardani, Ratna (STRADA : Jurnal Ilmiah Kesehatan, 2023)
Environment-based diseases contribute more than 80% of diseases experienced by infants and toddlers in Indonesia. This situation indicates that the coverage and quality of environmental health interventions in Indonesia is still low. The research objective is to analyze the effect of physical house sanitation on the incidence rate of ARI among children under five in Punjul Village Plosoklaten District, Kediri Regency. The design of this research is experimental quantitative research with the focus of the research being directed at analyzing the effect of physical house sanitation on the incidence rate of ARI among children under five in Punjul Village Plosoklaten District, Kediri Regency with a population of 46 respondents and a sample of 41 respondents who were drawn by the simple random sampling technique. The findings found that almost half of the respondents have good category physical sanitation as many as 15 respondents (36.6%).